PEMANFAATAN HEWAN SEBAGAI OBAT TRADISIONAL DALAM KEHIDUPAN SUKU HATTAM DI KAMPUNG MOKWAM MENYAMBOUW - Simon Sutarno; Amon A. Rumbino (FMIPA Universitas Papua, 2008)
This research aim to document traditional knowledge (indigenous knowledge) of the Hattam tribe in exploiting animals as traditional drug, in which the observation was done on the animal type, way of exploiting, and also on other culture and knowledge related to pattern of exploiting animals as drug in the life of the tribe. The result shows that there are 9 animals used as traditional drug in the life of the Hattam tribe in Mokwam village, that is: Rana grisea, Litoria arfakiana, Litoria micromembrana, Litoria angiana, Nyctimystes pulchra, Accipiter sp., Morelia viridis, Micropechis sp., and Sus sp. The animals were used as drugs to cure skin disease (purities), bloated, flatulent stomach, wounds, and in increasing vitality.